Rediscovery of an elusive species, Halpe sikkima Moore, 1882 (Hesperiidae, Hesperiinae) from Hainan, China - Xue, Guoxi; Lv, Hongkun; Yin, Weizhi; Li, Meng (Zootaxa, 2018)
Almost 70 years after its first record from Hainan by Evans in 1949, the second specimen of Halpe sikkima Moore, 1882 was found on the island. The male genitalia of this species are illustrated and re-described. The COI sequence is published for the first time.